North-South diffusion of climate-mitigation technologies: The crowding-out effect on relocation - Julie Ing; Jean-Philippe Nicolai (ETH Zurich, CER-ETH - Center of Economic Research, 2019)
The deployment of cleaner production technologies is crucial to mitigate the effect of climate change. The diffusion of technology from developed to developing countries can be done through different channels. It can be a business decision such as firms' relocation, creation of a subsidiary or the adoption of technology by southern firms, or it may be decided at government level. This paper investigates in a two-country model (North and South) the relationship between the firms' relocation and diffusion of mitigation technologies. We assume that both countries implement a carbon tax and there are two kinds of production technology used: a relatively clean technology and a dirty one. This paper theoretically shows that the diffusion technology by technology adoption, public transfer or subsidiary creation induces a decrease in relocation, while technology diffusion via purchasing dirty southern firms may increase the number of relocated firms. The paper also demonstrates that technology diffusion may have perverse effects in the long run. Indeed, total emissions may increase with technology diffusion since southern firms are more competitive.
Keywords: L13; Q53; Q58; 330; Technology transfer; Carbon tax; Relocation; Trade of polluting goods; Imperfect competition